Pengaruh Deskripsi Pekerjaan, Kompetensi, dan Self-Efficacy terhadap Produktivitas Karyawan di PT Kartika Inti Sejati - Amanda Putri Anandita; Ridlwan Muttaqin; Riyandi Nur Sumawidjaja (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The level of employee productivity is a crucial factor in determining a company's success and competitiveness. This study aims to analyze and empirically test the influence of three main factors: the clarity of Job Descriptions, the level of employee Competency, and Self-Efficacy on employee productivity at PT Kartika Inti Sejati. The research employed a quantitative approach with a causal survey design. The population of this study consisted of all employees at PT Kartika Inti Sejati. The sample was determined using a specific technique and analyzed using multiple linear regression methods. Classical assumption tests confirmed that the regression model was appropriate. The partial test results showed that Job Description, Competency, and Self-Efficacy each had a positive and significant effect on employee productivity. Furthermore, the simultaneous test confirmed that these three variables collectively and significantly influence the increase in employee productivity. The main conclusion is that improving the clarity of job roles, strengthening employee competency, and consistently cultivating employee self-confidence are effective strategies for the management of PT Kartika Inti Sejati to optimize overall company performance and output.